Autophagy and Apoptosis Induced in U87 MG Glioblastoma Cells by Hypericin-Mediated Photodynamic Therapy Can Be Photobiomodulated with 808 nm Light - Viktoria Pevna (MDPI AG, 2021)
Glioblastoma is one of the most aggressive types of tumors. Although few treatment options are currently available, new modalities are needed to improve prognosis. In this context, photodynamic therapy (PDT) is a promising adjuvant treatment modality. In the present work, hypericin-mediated PDT (hypericin-PDT, 2 J/cm2) of U87 MG cells is combined with (2 min, 15 mW/cm2 at 808 nm) photobiomodulation (PBM). We observed that PBM stimulates autophagy, which, in combination with PDT, increases the treatment efficacy and leads to apoptosis. Confocal fluorescence microscopy, cytotoxicity assays and Western blot were used to monitor apoptotic and autophagic processes in these cells. Destabilization of lysosomes, mitochondria and the Golgi apparatus led to an increase in lactate dehydrogenase activity, oxidative stress levels, LC3-II, and caspase-3, as well as a decrease of the PKCα and STAT3 protein levels in response to hypericin-PDT subcellular concentration in U87 MG cells. Our results indicate that therapeutic hypericin concentrations can be reduced when PDT is combined with PBM. This will likely allow to reduce the damage induced in surrounding healthy tissues when PBM-hypericin-PDT is used for in vivo tumor treatments.